IADC/SPE Drilling Conference and Exhibition 2014
DOI: 10.2118/168001-ms
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Studies of Wellbore Strengthening

Abstract: In drilling deep horizons, the mud weight window between pore pressure gradient and fracture gradient often narrows due to rock properties and underground stress state. Non-productive time (NPT) events such as lost circulation, wellbore instability, kicks, underground cross-flow, and pipe sticking are more likely. Such problems greatly increase drilling costs. Plugging preexisting natural fractures or drilling-induced fractures with lost circulation materials (LCM) is often used to increase fracture gradient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Therefore, it can be concluded that the closer the bridging location to the fracture aperture, the more effective stress cage technology. This result is in agreement with previous studies [23,26].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, it can be concluded that the closer the bridging location to the fracture aperture, the more effective stress cage technology. This result is in agreement with previous studies [23,26].…”
Section: Resultssupporting
confidence: 94%
“…Feng et al (2014) used two-dimensional elastic and poro-elastic models to evaluate the stress state at the near wellbore region before fracture initiation, during fracture propagation, and after fracture bridging with LCM. In the conclusion, authors provided a detailed description of the wellbore strengthening mechanism and affecting parameters [26].…”
Section: Introductionmentioning
confidence: 99%
“…Lost circulation is a major costly incident in the drilling and completion phases. Existing studies have indicated that lost circulation can be effectively mitigated by wellbore strengthening (Alberty and McLean 2004;Arlanoglu et al 2014;Zhao et al 2017). The above analysis has shown that increased FIP and thus wellbore strengthening can be achieved by forming a mudcake on the wellbore wall.…”
Section: Comparison With Fracture-bridging Wellbore Strengthening Methodsmentioning
confidence: 88%
“…The stress and rock properties are consistent with those used in Feng and Gray (2016b). For the fracture-bridging model, the commonly used 0.15-m (6-in) fracture length assumption is adopted (Alberty and McLean 2004;Arlanoglu et al 2014;Aston et al 2007;Wang et al 2009). The tensile strength is 15 MPa determined from the fracture toughness using Eq.…”
Section: Comparison With Fracture-bridging Wellbore Strengthening Methodsmentioning
confidence: 95%
“…Based on the basic principles, both the pre-drilling prediction and monitoring-while-drilling methods can be divided into two categories: normal compaction trend method and direct pressure prediction method [4][5][6][7][8][9][10][11][12] . In the normal compaction trend method based on formation under-compaction mechanism, a compaction trend line equation is built within the normal section using variations of acoustic, density, resistivity and other logging data along with the depth, and the formation pressure is predicted according to deviation of the actually measured value from the trend line.…”
Section: Conventional Pore Pressure Prediction Methodsmentioning
confidence: 99%